1976
DOI: 10.1016/0035-9203(76)90008-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in Trinidad and Grenada, with special reference to the mongoose

Abstract: In Trinidad, six Leptospira isolates were made from 957 febrile patients between 1968 amd 1972. In addition, CF antibodies were detected in 6-6% of febrile patients and human survey sera collected during this period. In 1972 alone, 10-4% (38/363) of sera examined had CF titres consistent with positive exposure to the disease. Grenada does not report leptospirosis, but the disease is common in mongooses in both Trinidad and Grenada. Serogroups Icterohaemorrhagiae, Pomona and Canicola are present in Grenada with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Our data agree with that of Sitprija et al (1985) who observed a high incidence of L. bataviae infection. The results from the West Indies, reported by Everard & Green (1976) are similar to those reported here.…”
Section: Discussionsupporting
confidence: 90%
“…Our data agree with that of Sitprija et al (1985) who observed a high incidence of L. bataviae infection. The results from the West Indies, reported by Everard & Green (1976) are similar to those reported here.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the seven serovars detected in the current study, five (Icterohaemorrhagiae Copenhageni, Icterohaemorrhagiae Icterohaemorrhagiae, Sejroe Sejroe, Ballum Ballum, and Bataviae Bataviae) have earlier been reported in human and animal infections or clinical leptospirosis in the country [26–28, 35, 38, 39]. …”
Section: Discussionmentioning
confidence: 91%
“…The organisms can exist in water and soil as detected in samples taken from rice fields, water channels, and rivers; these act as sources of infection for humans (Issazadeh et al 2008). While reservoir hosts may not display clinical signs when infected with particular serovars, infection of humans with these same serovars may result in illness and disease (Babudieri 2006;Everard and Green 1976).…”
Section: Introductionmentioning
confidence: 99%